Synthesis, Structure-Activity Relationships and Brain Uptake of a Novel Series of Benzopyran Inhibitors of Insulin-Regulated Aminopeptidase - Mountford, Simon J.; Albiston, Anthony L.; Charman, William N.; Ng, Leelee; Holien, Jessica K.; Parker, Michael W.; Nicolazzo, Joseph A.; Thompson, Philip E.; Chai, Siew Yeen (Journal of medicinal chemistry, 2014)
Peptide inhibitors of insulin-regulated aminopeptidase (IRAP) enhance fear avoidance and spatial memory and accelerate spatial learning in a number of memory paradigms. Using a virtual screening approach, a series of benzopyran compounds was identified that inhibited the catalytic activity of IRAP, ultimately resulting in the identification of potent and specific inhibitors. The present study describes the medicinal chemistry campaign that led to the development of the lead candidate, 3, highlighting the key structural features considered as critical for binding. Furthermore, the in vivo pharmacokinetics and brain uptake of compounds (1 and 3) were assessed in rats and were complemented with in vitro human and rat microsomal stability studies. Following intravenous administration to rodents, 3 exhibits brain exposure, albeit it is rapidly converted to 1, a compound which also exhibits potent inhibition of IRAP.